1997
DOI: 10.1007/s004310050642
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival impression cytology in the preterm infant and it's relation to outcome

Abstract: Conjunctival impression cytology is simple and reproducible technique which maybe easily applied to the preterm infant. Abnormal CIC is associated with retinopathy of prematurity requiring treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…Images in the literature indicate that similar confluent layers of cells can be obtained if a glass rod is used to exert pressure on an unsupported filter after applying it to the conjunctival surface (Nelson, 1982;Nelson et al, 1983;Adams et al, 1988;Knop and Bewitt, 1992a;Bhatia et al, 1995;Dogru et al, 1998). If the tip of a pair of forceps or tweezers, or similar, is used to exert pressure between the conjunctival surface and an unmounted filter then less confluent and irregular sheets of cells seem to be the more likely yield (Egbert et al, 1977;Tseng, 1985;Pfugfelder et al, 1990;Rolando et al, 1990;Knop and Brewitt, 1992a,b;Rivas et al, 1993;Hughes et al, 1997;Blodi et al, 1998;Blades et al, 1998), although reasonably sized sheets of cells can be obtained (Rivas et al, 1992;Blades et al, 1998;Bizzari et al, 1998a). Other investigators, even using a glass rod, have however reported difficulty in obtaining adequate numbers of cells off the bulbar conjunctiva (Connor et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Images in the literature indicate that similar confluent layers of cells can be obtained if a glass rod is used to exert pressure on an unsupported filter after applying it to the conjunctival surface (Nelson, 1982;Nelson et al, 1983;Adams et al, 1988;Knop and Bewitt, 1992a;Bhatia et al, 1995;Dogru et al, 1998). If the tip of a pair of forceps or tweezers, or similar, is used to exert pressure between the conjunctival surface and an unmounted filter then less confluent and irregular sheets of cells seem to be the more likely yield (Egbert et al, 1977;Tseng, 1985;Pfugfelder et al, 1990;Rolando et al, 1990;Knop and Brewitt, 1992a,b;Rivas et al, 1993;Hughes et al, 1997;Blodi et al, 1998;Blades et al, 1998), although reasonably sized sheets of cells can be obtained (Rivas et al, 1992;Blades et al, 1998;Bizzari et al, 1998a). Other investigators, even using a glass rod, have however reported difficulty in obtaining adequate numbers of cells off the bulbar conjunctiva (Connor et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…As amostras são fixadas, coradas e examinadas em laboratório, usando-se um método modificado para a citologia da superfície ocular. Esta técnica auxilia o entendimento e direciona o tratamento das afecções da superfície ocular, pois permite a análise do grau de metaplasia escamosa, contagem do número de células caliciformes em casos de olho seco, hipovitaminose A, deficiência límbica corneal (síndrome de Stevens-Johnson, penfigóide ocular, queimaduras) (3) ; utiliza-se como método de análise microbiológica (viral) (4)(5) e na avaliação da superfície ocular em pacientes usuários de lente de contato (6) , em bebês prematuros (7) , e em pacientes diabéticos (8) .…”
Section: Introductionunclassified
“…44 Pooled data show a non-significant trend towards a reduction in ROP in vitamin A supplemented infants. 12 The pathogenesis of ROP is complex and includes free radical mediated oxidative damage to the developing retina which could in theory be ameliorated by the antioxidant properties of vitamin A.…”
Section: Respiratory Functionmentioning
confidence: 94%
“…43 Microscopic conjunctival changes consistent with vitamin A deficiency have been noted in preterm babies, but the relation to vitamin A status was not explored. 44 The preterm infant retina at birth contains several times less rhodopsin than at term birth 45 ; how rapidly rhodopsin is subsequently accreted, and how this is related to total body stores of vitamin A, is not known. The rhodopsin content of the developing rat retina is dependent on vitamin A sufficiency and is reduced by early exposure to light.…”
Section: Respiratory Functionmentioning
confidence: 99%
See 1 more Smart Citation